POWER FACTOR IMPROVMENT FOR CEMENT FACTORY - Tawfeeq Enad Abdulabbas (Journal of Engineering and Sustainable Development, 2018)
The cement plant contains nonlinear loads and significant harmonic sources (kiln rectifiers drives) that can flow through the plant, therefore it is necessary to treat both the harmonics and the power factor reduction problems to improve the system efficiency, power system quality and decrease losses. This work examines the technical feasibility of designing a capacitor filter bank according to the level of harmonics in the network, and also achieving improvement for the power factor (Static Compensators). The methodology used for this work is based on the practical measurements of real-time operation of the electrical parameters of cement industrial facility, and then the whole system has been modeled (using MATLAB/SIMULINK). A MATLAB code is used to calculate the harmonic filter components required to design the capacitor filter to be then inserted in the simulated model in order to cross-check the load operation after insertion filter component via enabling different modes of operations. Also, system performance calculations are made after including the harmonic filters is to ensure the safety of the operations.